2023
DOI: 10.1097/sap.0000000000003471
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Impact of Patient Factors on BREAST-Q Outcomes After Reduction Mammoplasty

Abstract: Background As reduction mammoplasty rises in popularity, it will become increasingly important to understand the patient-reported outcome measurements associated with a successful operation. There has been a growing body of literature on BREAST-Q outcomes for patients undergoing reduction mammoplasty, but meta-analyses of patient factors and BREAST-Q Reduction Module scores are lacking. This study sought to ascertain which patient factors were associated with improvements in BREAST-Q scores compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
1
1
Order By: Relevance
“…Only self-esteem was associated with age and surgical procedure, with older women and those who underwent the procedure without implants exhibiting lower levels of self-esteem. This contrasts with the review conducted by Liao et al (2023) , which observed that older age correlated with higher scores of sexual well-being before the intervention, suggesting that older patients generally have greater self-confidence. While our results did indicate that the older age group had higher scores in sexual well-being and two factors of sexual desire, the differences were not statistically significant compared to the younger age group.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Only self-esteem was associated with age and surgical procedure, with older women and those who underwent the procedure without implants exhibiting lower levels of self-esteem. This contrasts with the review conducted by Liao et al (2023) , which observed that older age correlated with higher scores of sexual well-being before the intervention, suggesting that older patients generally have greater self-confidence. While our results did indicate that the older age group had higher scores in sexual well-being and two factors of sexual desire, the differences were not statistically significant compared to the younger age group.…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, post-intervention, no relationship was observed between age groups and self-esteem, nor was there any association between self-esteem and the surgical procedure. This, however, aligns with Liao et al (2023) , which suggested that the positive impact of breast reduction surgery is evident across all BREAST-Q domains regardless of age.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation